Performance of Aerated Autoclaved Brick Masonry Walls Strengthened by Plaster with GFRP Net and Fibers - TÜRK, AHMET MURAT (My University, 2018)
Recently, the autoclaved aerated concrete (AAC) has increased its popularity in construction industry where its lightness, thennal insulation properties and workability are particularly appreciated. Mainly, its lightness attracts more interest for the use of infill/partition walls of framed structures in highly seismic areas like Turkey. Such walls are usually covered by plaster for obtaining smooth surfaces for indoor areas. For better performance of plaster and increasing the cracking strength of these walls, plaster nets are utilized frequently. Plaster nets are usually made of GFRP material and keeps a potential tensile strength and deformation capacity when compared to plain plasters. To investigate the effect of the use of AAC brick walls for the new/existing structures by utilizing GFRP plaster nets and fiber added plaster is the main goal of this experimental study. The test results are discussed to investigate the effect of AAC brick wall strengthened by using inexpensive GFRP mesh and fiber on the behavior and mechanical properties of walls where wall specimens are prepared by employing different parameters like the use of GFRP mesh, use of plaster and the use of fiber wall plaster. By using diagonal tension testing method of wall specimens, the load carrying capacity comparisons are made. The results turned out to be highly promising. Significant increase in shear strength and deformation of strengthened walls in comparison with plain (reference) walls is observed. The tests also showed a positive effect of GFRP reinforcement on the failure mode of these walls.
Keywords: Autoclaved aerated concrete (AAC); Masonry; Infill Wall; Glass Fiber Reinforced Polymer (GFRP)